The Theatricalization of the Image in Al-Hariri’s Maqamat - اللامي أ.م.د زمان عطا نجم (Thi Qar Arts Journal, 2024)
Al-Hariri’s Maqamat are a type of prose characterized by its deep language, variety of derivations, and rhythmic phrases that harmonize with the words. For these reasons and more, they represent an artistic piece in which multiple images—visual, linguistic, and narrative—are manifested.